Obedience of iron tablet consumption reduces risk of anemia among Indonesian female adolescents - Anjarwati Anjarwati; Siti Ruqoiyah (Universitas Aisyiyah Yogyakarta, 2020)
Female adolescents have more risks to experience anemia when they have prolonged menstruation, frequent consuming tea, have inadequate iron consumption, have menstrual disorders. The purpose of this research was to investigate the relationship of iron tablet consumption obedience with the incidence of anemia among female adolescents in Yogyakarta, Indonesia. This research used cross sectional study. Sampling techniques was using random sampling. Analysis method with Chi square test. The results showed that majority of female adolescents were lack of obedient in consuming iron tablets of 47%. The number of female adolescents were suffered from anemia i.e. 59%. It can be concluded that there was a correlation between the consumption obidience of iron tablets and the incidence of anemia in female adolescents with P value 0.000.